TEACHING PHYSICS FOR NON-PHYSICS SPECIALITY ON MODULAR TECHNOLOGY - Farmonov, Utkir (Физико-технологического образование, 2024)
In the present article we considered the problem of application of modular educational technology in teaching process of physics for non-physics specialty students. It is given a comparative analysis of the mechanisms of teaching physics based on modular technology in higher education system